Reproductive Outcomes of Transferring Blastocysts Derived From Frozen–Thawed Cleavage Embryos: A Systematic Review and Meta‐Analysis - Huy Phuong Tran; Nam Nhat Nguyen; Ngoc Thanh Truong; Tuyet Thi‐Diem Hoang; Trang Nguyen‐Khanh Huynh; Ha Le‐Bao Tran (Reproductive Medicine and Biology)
ABSTRACT Background In in vitro fertilization (IVF), transferring frozen–thawed blastocysts is a widely adopted practice. This meta‐analysis aims to evaluate the reproductive outcomes of transferring blastocysts derived from frozen–thawed cleavage embryos (FT‐CDB group) compared to direct frozen–thawed blastocyst (DFB group) transfers. Methods We searched the following electronic databases for relevant studies: PubMed/MEDLINE, EMBASE, Scopus, and Web of Science. Studies were included if they compared the clinical and neonatal outcomes of IVF patients receiving either FT‐CDB or DFB transfer with vitrification method. The protocol for this review has been registered in PROSPERO. Results A total of seven studies (2057 patients) were included in the analysis. Participants in the FT‐CDB group demonstrated significantly higher odds of achieving clinical pregnancy (OR 1.24, 95% CI 1.03–1.49, p = 0.022, I2 = 27%), and live birth (OR 1.31, 95% CI 1.08–1.60, p = 0.007, I2 = 0%) compared to the DFB group. No significant differences were observed in the birth weights of infants between the groups (MD −87.05 g, 95% CI −293.77 to 119.67, p = 0.41, I2 = 83%). Conclusion Transferring blastocysts derived from frozen–thawed cleavage embryos is associated with higher odds of clinical pregnancy and live birth compared to frozen–thawed blastocyst transfers. Trial Registration PROSPERO number: CRD42024591620